PEMBIAYAAN SYARIAH SEBAGAI KATALISATOR PERTUMBUHAN UKM DI ERA EKONOMI INKLUSIF - Agustina Damanik; Raden Sardiman Pratama; Layla Hanum Abung (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the role of Islamic financing as a catalyst for the growth of Small and Medium Enterprises (SMEs) in the context of an inclusive economy. Using a qualitative-descriptive approach based on field studies, data was obtained through in-depth interviews with SME actors, managers of Islamic financial institutions (IFIs), and observations of financing practices in the field. The results show that Islamic financing contributes significantly to expanding access to capital for SME actors, especially those in the informal sector who are underserved by conventional financial institutions. Through contracts such as murābaḥah, mudhārabah, and musyārakah, IFIs not only provide business capital but also instill sharia-based business ethics. However, the effectiveness of Islamic financing still faces structural challenges such as limited financial literacy, low mentoring capacity, and lack of policy integration. This study confirms that Islamic financing has great potential as a driver of equitable and sustainable SME growth in an era of inclusive economy.